On the use of entropy in Markovian model of rainfall (MAUSAM, 1994)
A statistical study of the annual rainfall data at Cocch Behar district during the periodt90 1 to t9S ~ has been undertaken by using. Markov chain model. One step 3 X3 Ma rcov chain model has beenused in (his study. The outcomes of the model reveal normal, bad and good year of rainfall a t the two stationsof thi s district. The hypoth esis of independence has been tested on the use of entropy and it has been ver ifiedusing likelih ood ra tio criterion. The results of the two methods are the same-tha t the yearly rainfall occurrencemay be regarded as independent at the two places o f the district.